Em tempos de AIDS no Brasil: veja, sexualidade e um nó nos costumes (1981 – 1992) - Moreira, Lucas de Sousa (2024)
In 1981, the first signs of the emergence of a new disease at an international level arrived in Brazil. This disease, which during its early years was covered by several symbolic representations, became one of the greatest challenges of science that, during the second half of the XX century, proved to be unbeatable in combating diseases, such as syphilis and leprosy. AIDS, Acquired Immunodeficiency Syndrome, as it will be called from 1983 onwards, mobilized different sectors of international society, as well as enabling the reflection of different social aspects in the society in which it manifested itself. This dissertation seeks to problematize the ways in which discourses about sexuality are mobilized by the narratives of the disease exposed in editions of Veja magazine, between the years 1981 and 1998. As it is a magazine with national circulation, the weekly magazine allows us to think historically about the ways in which narratives about AIDS became a discursive proliferation about sexuality in Brazil. From the perspective of implicit and explicit power relations in the speeches, we will work with the theoretical dimensions that come from the contributions of Cultural History, based on Roger Chartier 's compressions on representations, as well as, on the productions of power and knowledge from the understanding of Michel Foucault. We intend to understand how discourses about the disease forged a knowledge that sought control not only over bodies, but also over sexual culture. We keep in mind that the story writing process takes specific procedures into consideration. Thus, when contextualizing this research, we keep in mind that one of the concerns of Social History relates to the perception of changes, oscillations and cohesion between social mechanisms.